A organização do ensino em ciclos e as demandas para a gestão em escolas públicas estaduais na cidade de São Paulo - Brisac, Clareane Lima Carneiro (2010)
The teaching organization in cycles, in Brazil, was already, certainly, among main discussions for educational scope. This innovation foresees changes in time and school space changing the organization process of teaching. Implanted in 1998 by Resolution SE n° 4/98, the regime of continued progression is organized in two cycles: Cycle I, correspondent to the four first series, and Cycle II, to the four last series of the fundamental teaching. This research had as object the demands for the school administration originating of the teaching organization in cycles and the practice of predominant school administration in a public net school of São Paulo. Our objective were: Identify and to analyze the teaching organization demands in cycles from the legislation on the theme and of the practice of the school administration in a cycle's I and cycle school II, located in the south zone district of São Paulo; Verify, empirically, how the administrative practice nowadays developed at school attends the teaching organization demands in cycles; Identify and to describe the necessary modifications in school organization and administration that can contribute favorably for the improvement of the school process (teaching quality). The demands for the School Administration were identified by means of a qualitative research with the literature revision that has the teaching organization in cycles as thematic and legal documents that organized and instituted this organizations in São Paulo's State Public net. The administration practice was searched by personal interviews with school managers and practices observation of school administration in a cycle's I school (1st to the 4th series) and cycle II (5th to the 8th series) of the Fundamental Teaching, that makes part of the Directory Center-west (capital) of São Paulo's public net. For so much, they were prioritized some categories as evaluation, recovery, school work, collective, school collegiate work, performance indicators.